Career anchors : discovering your real values - Schein, Edgar H. 4 0 16; 5 (San Francisco : Pfeiffer & Company, 1990)
Provides activities and instructions designed to help individuals determine their career anchor--a combination of perceived areas of competence, motives, and values that cannot be compromised,and includes a definition of the nature of career anchors, discussion of career development, and descriptions of eight career anchor types.
Includes bibliographical references.
Adult.
Keywords: 2 -- 0; 6; Vocational guidance; 20; 2